40th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2004
DOI: 10.2514/6.2004-3610
|View full text |Cite
|
Sign up to set email alerts
|

Post-Test Analysis of the Deep Space 1 Spare Flight Thruster Ion Optics

Abstract: The Deep Space 1 (DSl) spare flight thruster (FT2) was operated for 30,352 hours during the extended life test (ELT). The test was performed to validate the service life of the thruster, study known and identify unknown life limiting modes. Several of the known life limiting modes involve the ion optics system. These include loss of structural integrity for either the screen grid or accelerator grid due to sputter erosion from energetic ions striking the grid, sputter erosion enlargement of the accelerator gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…By examining the beam profiles and radial dependence of grid erosion observed during the ELT [7], it is apparent that the changes in screen grid ion transparency observed during the ELT must be primarily caused by erosive thinning of the screen grid that predominately occurred near the center region of the overall grid area. Therefore, increases in screen grid ion transparency over the life of the thruster at the center gridlet (as observed in the ELT results discussed later) should be much higher than that of the entire beam.…”
Section: B Electron Backstreaming Integration Over Single Gridlets Amentioning
confidence: 98%
See 1 more Smart Citation
“…By examining the beam profiles and radial dependence of grid erosion observed during the ELT [7], it is apparent that the changes in screen grid ion transparency observed during the ELT must be primarily caused by erosive thinning of the screen grid that predominately occurred near the center region of the overall grid area. Therefore, increases in screen grid ion transparency over the life of the thruster at the center gridlet (as observed in the ELT results discussed later) should be much higher than that of the entire beam.…”
Section: B Electron Backstreaming Integration Over Single Gridlets Amentioning
confidence: 98%
“…Posttest analysis of the NSTAR thrusters at the conclusion of the LDT and ELT tests showed that the center region of the grids experienced the most erosion and accelerator grid aperture enlargement, features which lead to increased electron backstreaming [1,7]. This worst-case erosion was simulated in [6] for the full duration of the ELT.…”
Section: A Inputs and Gridlet Potential Solutionsmentioning
confidence: 99%
“…Posttest mass measurements of the screen and accelerator-grid assembly made with a high-precision balance concur with the profilometry calculations to within 2 and 10%, respectively, thereby validating the profilometry mapping technique and subsequent data analysis performed [18].…”
Section: Posttest Inspectionmentioning
confidence: 99%
“…Analytical and computational analysis [17] is also associated with the posttest analysis, including a finite element model analysis of the stresses experienced by the grids during operation. A more detailed quantitative analysis of the ion-optics wear and posttest condition, as well as measurement techniques used, can be found in [18].…”
Section: Posttest Inspectionmentioning
confidence: 99%
“…The NSTAR screen grid apertures only exhibited slight chamfering on the upstream side during the 8200 hour test 6 and less than 60 µm of chamfering during the NSTAR ELT. 51 It is possible to correlate the net erosion of the screen grids between the NSTAR thruster and the NEXT thruster. The net erosion on the screen grid per mass of propellant throughput, shown in Eq.…”
Section: E Screen Grid Erosionmentioning
confidence: 99%